Коллекция восточного холодного оружия из фондов Бахчисарайского заповедника - Остапенко, Г.Д. (Культура народов Причерноморья, 2013)
В данной статье рассматривается коллекция восточного холодного оружия с длинным
клинком из фондов Бахчисарайского заповедника, как пример развития оружейного дела на Востоке в
XVIII веке. Исследуемый материал дает представление о вооружении восточного война. Описание
некоторых экземпляров сделано с целью показать уровень качества и высокохудожественного
достоинства старинного восточного оружия. У даній статті розглядається колекція східної холодної зброї з довгим клинком з фондів
Бахчисарайського заповідника, як приклад розвитку збройової справи на Сході в XVIII столітті.
Досліджуваний матеріал дає уявлення про озброєння східного воїна. Опис деяких екземплярів зроблено з
метою показати рівень якості та високохудожньої гідності старовинної східної зброї. One of the oldest artifacts of material culture is cold weapon that people have used for military
purposes and in everyday life. Eventually weapons were improved and separated from the tools, serving for
defense and attack. The Collection of Oriental cold weapons of Bakhchisaray preserve was formed from several
sources in the 20’s-70’s of the 20th century. In 1919-1925, 18 items of Oriental cold weapons were received and
purchased by the funds of the Museum from the private collections of B.D. Lavrov, M.M. Dremdzhi, B.
Bakshishev, Y.A. Danilov. In 1925, the collection of weapons was enriched by 8 items which came from the
Central Museum of Taurida. The most significant inflow of weapons took place in 1950 from the Artillery
Historical Museum (Leningrad) and in 1957 from the Hermitage. In different years (1952 - 60), the sporadic
receipts were made from Crimean museums: Alupka and Oriental museums; Kokkoz Yusupov Palace. In 1968,
Odessa Regional Museum has sent several (3) units of cold weapons to Bakchisaray Museum. In last years the
collection of weapons was enriched with exhibits from the Crimean customs (6 items).
Traditionally the cold weapon is divided into three main groups: bladed, spear, hammer. There are other
classifications: by type of the cold weapon action, features and techniques of usage, etc. Unfortunately, the
oriental spear (5 items) and hammer (5 items) weapons фare represented by few examples in the collection of
Bakhchisaray preserve. The attention of this article is given to the solid in size and varied by structure collection
of oriental weapons with long blade (34 items), which is of interest not only as examples of weapons , but also
as a highly artistic works of the gunsmiths. Most of the oriental long blade weapons of Bakhchisaray preserve
collection is represented by the sabers “shemshir” (10 items). All of them dated the 18th century and were made
in Turkey and Iran.
This work is the first attempt in research of old weapons as one of the large and unique collections of historic
funds of Bakhchisaray preserve.